2020
DOI: 10.1038/s41541-020-00242-y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of four new B-cell protective epitopes for malaria using Q beta virus-like particle as platform

Abstract: Malaria remains one of the world’s most urgent global health problems, with almost half a million deaths and hundreds of millions of clinical cases each year. Existing interventions by themselves will not be enough to tackle infection in high-transmission areas. The best new intervention would be an effective vaccine; but the leading P. falciparum and P. vivax vaccine candidates, RTS,S and VMP001, show only modest to low field efficacy. New antigens and improved ways for screening antigens for protective effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…In summary, the results obtained indicated that the bivalent chimeric RHDV VLPs allowed good simultaneous immunogenicity for both target B-cell epitopes tested, in agreement with previous reports with other chimeric VLPs [42,[45][46][47]. Interestingly, RHDV VLPs have been recently reported to efficiently co-deliver two T-cell epitopes (cancer antigens), inducing a targeted anti-tumour immune response [14,15], further extending the feasibility of using the RHDV vaccine platform for the co-delivery of multiple antigens.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In summary, the results obtained indicated that the bivalent chimeric RHDV VLPs allowed good simultaneous immunogenicity for both target B-cell epitopes tested, in agreement with previous reports with other chimeric VLPs [42,[45][46][47]. Interestingly, RHDV VLPs have been recently reported to efficiently co-deliver two T-cell epitopes (cancer antigens), inducing a targeted anti-tumour immune response [14,15], further extending the feasibility of using the RHDV vaccine platform for the co-delivery of multiple antigens.…”
Section: Discussionsupporting
confidence: 89%
“…Several VLP-based platforms have been proposed as scaffolds for multi-target antigen presentation [40][41][42][43][44][45][46][47]. Potential concerns faced by multivalent vaccines are issues related to immune interference and epitope dominance, as numerous reports have shown that co-immunization with multiple antigens can induce immune interference, affecting both antigen specific B cell responses and T cell responses [48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody responses to each of these three proteins have been detected in individuals naturally infected with either P. falciparum or P. vivax (54)(55)(56). However, unlike PF08_0081 and PF14_0593, B cell epitopes specific for PFD0430c have yet to be identified (57), despite that fact that of the three proteins PFD0430c is the best characterized. PFD0430c was first identified by transcriptome analysis of P. yoelii salivary gland sporozoites, and was located in the microneme (58).…”
Section: Discussionmentioning
confidence: 99%
“…VLPs can be expressed in insect [32,47], mammalian [48,49], bacterial [50], plant [37,51] or yeast cells [33]. These particles have been used for the development of vaccines against several infectious diseases [52].…”
Section: Introductionmentioning
confidence: 99%